Discovering the creativity of written works: the keywords study. Issue 1 (3rd July 2019) - Turkman, Burak; Runco, Mark A.
ABSTRACT: This study investigated how creativity reveals itself in written language and showed that creative ideas can be identified in written works by discovering words and phrases (keywords) that are used to introduce new ideas. Additionally, this study sought to find a solution to alleviate creativity's laborious scoring procedure. The sample included undergraduate level students from a large state university in the Southeastern United States majoring in various fields and the study utilized expert judges using the Consensual Assessment Technique. This keywords study found specific words and phrases that are used with regularity when people introduce a new idea. The study provided an understanding of how creativity is expressed in written works and the keywords were tested by using different sources of writing and transcribed speeches. Expert judges and resulting statistical analyses indicated that specific keywords successfully identified original ideas in written language samples. The findings of this keywords study brought an original and objective method to finding what words or phrases introduce original ideas.